A comparison between two methods of generating power, heat and refrigeration via biomass based Solid Oxide Fuel Cell: A thermodynamic and environmental analysis. (15th October 2016) - Mortazaei, M.; Rahimi, M.
Highlights: Two novel trigeneration systems based biomass and Solid Oxide Fuel Cell are compared. A complete environmental analysis for three different cases is conducted. Digester based system has 14.56% more exergetic efficiency than gasifier based one. Gasifier based system has 14.31% more energetic efficiency than Digester based one. Gasifier, Digester and air heat exchanger have the highest exergy destruction. Abstract: Utilization of biomass energy is of prevalence focus these days. Using these fuels to run the fuel cells is of primary interest. In this regard, two new trigeneration systems (producing power and heating alongside with cooling) based on solid oxide fuel cell fed by either the syngas or biogas are proposed. The performance of systems is analyzed and compared with each other from the thermodynamic viewpoint. Applying the conservation of mass and energy as well as the exergy for each system component and using the engineering equation solver, the system's performance are modeled. Through a parametric study, the effects of some key variables such as the current density and the fuel utilization factor in the systems' performance are investigated. In addition, considering the system as a combination of three subsystems, that is, the power generation system, heat and power generation system and trigeneration system, an environmental impact assessment in terms of Carbon dioxide emission is carried out for both digester based Solid Oxide Fuel Cell and gasifier based one. It is observed that using biogas from digester leads to more exergetic (which is 14.56%) and less energetic efficiency (Which is 14.31%), with a Carbon dioxide emission of 17.87 ton/MW h for the tri-generation system. The value of this parameter is 21.32 ton/MW h when gasifier is used as the supplier of fuel for solid oxide fuel cell.